NON LINGUISTIC ASPECT CAUSED STUDENTS’ FOREIGN LANGUAGE ANXIETY IN SPEAKING ENGLISH - Saleh, Yuwin Rustam; Akhmad, Enni; Akhmad, Zulkifli (English Review: Journal of English Education, 2023)
Foreign language anxiety is a type of anxiety that is experienced by individuals when learning, speaking, or interacting in a foreign language. Some scholars have been interested to investigate the foreign language anxietyin the classroom and identified the cause of students’ foreign language anxiety, either in international context or Indonesia context. Most of the factors related to the linguistic aspect, such as students lack vocabulary, students lack of pronunciation, and do not understand of teacher’s talk. However, the research about factors of foreign language anxiety is caused by non-linguistic aspect was still undergrown. This research came to stipulate the gap of knowledge. This research used qualitative method and study case design. It took 20 students of English Education Department FITK IAIN Sultan Amai Gorontalo who have Upper-Intermediate proficiency level. The instruments of research used foreign language anxiety scale to identify factors of students’ foreign language anxiety and in-depth interview to know the students’ reason of being anxiety in foreign language classroom. It used triangulation method in analysing data, namely reducing data, displaying data, and drawing conclusion. The results showing that there were 3 non-linguistic aspects in causing students’ foreign language anxiety. First, they felt worried if they had to speak in front of the class and answered the lecturer's questions voluntarily. Second, they felt worried if they do not understand what the lecturer is talking about. Third, they felt worried if they did not prepare before the lesson started. Fourth, students felt worried if they would get a bad score. This result implied to the teacher’s technique in asking the students to speak in front of the classmate. Therefore, the research suggested to apply small group discussion in teaching and learning speaking skill in foreign language classroom.